An Intriguing Case of Eosinophilia with FIP1L1/PDGFRA Rearrangement Who Presented as Thrombotic Thrombocytopenic Purpura. (15th October 2019) - Alshehri, Hassan; Alnomani, Mohammad; Alghamdi, Mubarak; Motabi, Ibrahim; Tailor, Imran; Alshehry, Nawal; Alfayez, Mansour; Zaidi, Abdul Rehman Z.; Altaf, Syed; AlSwayyed, Azizah; AlSughayyer, Ammar; Zaidi, Syed Z. A.
Abstract : Myeloid neoplasm with eosinophilia and FIP1-like-1-platelet-derived growth factor receptor-alpha (FIP1L1-PDGFRA) rearrangement is a multi-organ disease with diverse clinical presentation. Thrombotic thrombocytopenic purpura (TTP) is characterized by the concomitant occurrence of often severe thrombocytopenia, microangiopathic hemolytic anemia, and a variable degree of ischemic organ damage. To our knowledge, only one case of eosinophilia with FIP1L1-PDGFRA rearrangement presented as a case of thrombotic thrombocytopenic purpura reported in the literature. We herein report a case of a young male patient with hypereosinophilic syndrome and FIP1L1-PDGFRA rearrangement who presented with asthma, transient ischemic attacks (TIA), and confusion. He had an acquired TTP that was successfully treated with plasma exchanges (PLEX), corticosteroids, rituximab, and later with the addition of imatinib mesylate (Gleevec, Novartis). He remains in complete remission on imatinib 100 mg daily for more than 28 months of follow-up.